Dry Powder Inhalation for Lung Delivery in Cystic Fibrosis - Xiaoxuan Han; Danni Li; Felisa Reyes-Ortega; Elena K. Schneider-Futschik (MDPI AG, 2023)
Pulmonary drug delivery has long been used for local and systemic administration of different medications used in acute and chronic respiratory diseases. Certain lung diseases, such as cystic fibrosis, rely heavily on chronic treatments, including targeted lung delivery. Pulmonary drug delivery possesses various physiological advantages compared to other delivery methods and is also convenient for the patient to use. However, the formulation of dry powder for pulmonary delivery proves challenging due to aerodynamic restrictions and the lower tolerance of the lung. The aim of this review is to provide an overview of the respiratory tract structure in patients with cystic fibrosis, including during acute and chronic lung infections and exacerbations. Furthermore, this review discusses the advantages of targeted lung delivery, including the physicochemical properties of dry powder and factors affecting clinical efficacy. Current inhalable drug treatments and drugs currently under development will also be discussed.